Intellectual Disability Associated With Pyridoxine-Responsive Epilepsies: The Need to Protect Cognitive Development - Hassel, Bjørnar; Rogne, Ane Gretesdatter; Hope, Sigrun (Frontiers in Psychiatry, 2019)
Pyridoxine (vitamin B6)-responsive epilepsies are severe forms of epilepsy that manifest as seizures immediately after birth, sometimes in utero, sometimes months or years after birth. Seizures may be treated efficiently by life-long supplementation with pyridoxine or its biologically active form, pyridoxal phosphate, but even so patients may become intellectually disabled, for which there currently is no effective treatment. The condition may be caused by mutations in several genes (TNSALP, PIGV, PIGL, PIGO, PNPO, PROSC, ALDH7A1, MOCS2, or ALDH4A1). Mutations in ALDH7A1, MOCS2, and ALDH4A1 entail build-up of reactive aldehydes (α-aminoadipic semialdehyde, -glutamic semialdehyde) that may react non-enzymatically with macromolecules of brain cells. Such reactions may alter the function of macromolecules, and they may produce ‘advanced glycation end products’ (AGEs). AGEs trigger inflammation in the brain. This understanding points to aldehyde-quenching, anti-AGE, or anti-inflammatory therapies as possible strategies to protect cognitive development and prevent intellectual disability in affected children. Studies on how aldehydes traverse cell membranes and how they affect brain function could further the development of therapies for patients with pyridoxine-responsive epilepsies.